Legal Analysis of the Cancellation of the Execution of Collateral in Supreme Court Decision MA 920K/Pdt/2020 - Farly Kanserano Jabiy (Fakultas Hukum Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze the execution of judgments in Indonesian civil law, particularly in relation to security rights and the parate executie mechanism as regulated in Law No. 4 of 1996.The method used in this study is a normative legal approach with a literature review, analyzing relevant legislation, court decisions, and implementing regulations. The main focus of this study is to explore the challenges and distortions that occur in the implementation of parate executie, which is actually designed to provide convenience, legal certainty, and efficiency for creditors.The novelty of this study lies in its in-depth assessment of the conflict between the provisions of the UUHT and court decisions and Supreme Court Circular Letters that hinder the implementation of parate executie without court intervention.The results of this study show that although the UUHT gives creditors the authority to directly execute collateral, in reality, legal uncertainty, complicated bureaucracy, and decisions that contradict the spirit of the UUHT actually slow down the execution process and increase losses for creditors. Therefore, this study recommends improving implementing regulations and revising related regulations, including canceling or revising Supreme Court Circular Letter No. 7 of 2012, so that the objectives of the UUHT to provide fast, inexpensive, and efficient execution can be achieved.The conclusions of this study are expected to contribute to the development of Indonesian civil law, particularly in strengthening legal certainty in the execution of security rights.